Thyroid cancer burden and risk factors in China from 1990-2019: a systematic analysis using the global burden of disease study - Jin, Shuai; Luo, Li; Xu, Xiaodong; Xia, Kaide (Frontiers in Oncology, 2023)
Background: Thyroid cancer (TC) is the most common endocrine system malignancy with a rapidly increasing incidence in China. Epidemiological data on TC at the national level are lacking. This study aimed to quantify the TC disease burden in China between 1990 and 2019 and evaluate the current status and trends of the disease burden attributed to a high body mass index (HBMI).Methods: The 2019 Global Burden of Disease Study dataset was used to explore the TC disease burden. Age-standardized rates of incidence (ASIR), prevalence (ASPR), deaths (ASDR), and disability-adjusted life years (DALYs) were considered and the estimated annual percentage change (EAPC) was calculated as a measure of the average change in age-standardized rates. The trend in TC-related mortality and DALYs attributed to an HBMI, accounting for different age groups and sexes, was examined.Results: Between 1990 and 2019, the ASDR and DALYs for TC decreased by 0.02/100000 and 1.17/100000, respectively. The ASPR and ASIR increased by 9.88/100000 and 1.04/100000, respectively. The EAPC for ASDR, age-standardized rates of DALYs, ASPR, and ASIR were 0.06 (95% CI: -0.09, 0.21), -0.20 (95% CI: -0.31, -0.10), 3.52 (95% CI: 3.35, 3.68), and 2.73 (95% CI: 2.58, 2.88), respectively. TC-related deaths, DALYs, and their prevalence and incidence in China increased by 118%, 350%, 81%, and 290%, respectively. The disease burden of TC was higher among male than female patients in different age groups, with varying distributions.The disease burden attributed to HBMI gradually increased over the past 30 years according to age-standardized DALYs, particularly in male patients.The TC burden has increased in China over the past 30 years, and population aging poses a challenge to TC prevention and control. HBMI has become an important factor in the TC disease burden and further research should focus on reducing the disease burden among Chinese male patients with TC.